Analisis Willingness To Pay (WTP) Terhadap Skenario Aspek Teknis Dan Alam Hutan Kota Dalam Pengelolaan Berkelanjutan (Studi Di Hutan Kota Palu)” - aminudin, Rifkal; Umar, Syukur; Muis, Hasriani (Universitas Tadulako, 2022)
This research aims to identify visitors' perceptions of the environmental conditions of urban forests and calculate the WTP value for efforts to maintain forest environmental conditions. Using the CVM method is a survey technique to ask respondents about the value/price they give to commodities that do not have a market price, such as environmental goods. The results obtained, Respondents' Perceptions were assessed from several aspects, namely: Cleanliness, Beauty, Comfort, Coolness and Satisfaction. With respondents' average rating being